Alimentação saudável com história em quadrinhos no ensino fundamental: um prato cheio de informação e diversão - Guida, Vânia Marília Lima (2024)
A healthy diet helps prevent various diseases, especially chronic ones, since the initial stages originate in childhood and adolescence. Poor nutrition at this stage of life can cause deficiency diseases, which leave the body more vulnerable to infectious diseases, such as diarrhea and flu. These can compromise the maturation of the central nervous system, with consequences at different levels of severity. Therefore, making food choices requires some types of information that serve as guidance regarding the most appropriate and healthy foods and eating practices, depending on the age group and needs. Food and Nutrition Education (EAN), the National Common Curricular Base (BNCC), with the transversal theme of health, and the Food Guide for the Brazilian Population (GAPB) direct the paths that can be taken in Science classes, in order to disseminate this knowledge and improve elementary school students' understanding of adequate and healthy eating and its importance for quality of life. The objective of this research was to evaluate the contributions of a Comic Book (COMIC) for 5th year elementary school students as a teaching resource on adequate and healthy eating. The research field was a municipal public school, of Elementary Education I, located in the East Zone of the city of Manaus, (AM). The research was qualitative and involved the following steps: bibliographical research, school lunch documents, anthropometric data from the research subjects and pedagogical intervention through a Didactic Sequence and 3 Pedagogical Moments, with pedagogical material. The results revealed the perceptions about what a healthy diet is, the Didactic Sequence (SD) together with the comic aroused the students' interest and when analyzing the textbook it was possible to verify that it presents the Food Guide for the Brazilian Population, however the 1st edition, even though it already has a 2nd edition. Through this research it was possible to positively contribute to students reflecting on the importance of knowing and discussing food issues, their importance in each person's life and that in public schools, school meals are not simply a matter of satisfying hunger, but rather contribute to the formation of good habits and eating autonomy.